Aflatoxin B1, Total Aflatoxin and Ochratoxin A Levels in Wheat Flour - KEMAL BUYUKUNAL, SERKAN; VURAL, AYDIN (Asian Journal of Chemistry, 2010)
In this study, 100 wheat flour specimens were analyzed with the ELISA technique regarding the amounts of total aflatoxin (AF), aflatoxin B1 (AFB1) and ochratoxin A (OTA). The AF, AFB1 and OTA contaminations in the specimens were found to be 71, 57 and 87 %, respectively. The specimens with AF and AFB1 levels exceeding the maximum limits defined by the Turkish Food Codex and European Commission constituted 5 % of all, while the OTA contents did not exceed the allowed limits in any of the specimens that have been examined.